Medicinal Plants with Potent Anti-inflammatory and Anti-arthritic Properties found in Eastern Parts of the Himalaya: An Ethnomedicinal Review - Banik, Bapan; Das, Sanjoy; Das, Malay Kumar (Pharmacognosy Reviews)
Since ancient times, medicinal plants performing a very essential role as a source of medicine and their medicinal properties have been well documented in the various traditional systems of medicine including Indian, Chinese and Korean medicines for the management of chronic inflammatory disorders. Arthritis is one of the harmful chronic inflammatory diseases and its pain vastly affects millions of people throughout the world. The inflammatory process of arthritis can stride very promptly causing swelling and destroying bone or cartilage cross the joints by various inflammatory mediators. Presently most commonly prescribed medication for the management of inflammation or arthritic pain is the NSAIDs, DMARDs and corticosteroids. Their prolonged use may cause a high spectrum of toxic effects. Hence, there is a demanding need to develop alternative therapeutic agents with minimum toxic effects. The Eastern Himalayan region is richly furnished with multifarious medicinal plants with potent anti-inflammatory and/ or anti-arthritic properties that have been traditionally used by the local people. Few studies have been convened in Himalayan medicinal plants to validate their medicinal values. Thus, from the knowledge of traditional medicine and research on plant materials, one might be able to discover newer and cost-effective drugs for treating diverse forms of inflammation. This review highlights the medicinal plants from the Eastern Himalayan region which showed promising therapeutic activity against inflammatory diseases as well as novel formulation approaches of these medicinal plants.
Keywords: Medicinal plants; Traditional medicine; Eastern Himalayan region; Inflammatory mediators; Anti-inflammatory; Anti-arthritic